Arabidopsis plants engineered for high root sugar secretion enhance the diversity of soil microorganisms. Issue 11 (31st July 2022) - Song, Min; Zhang, Xingjian; Yang, Jintao; Gao, Chen; Wei, Yahong; Chen, Shaolin; Liesche, Johannes
Abstract: Plants secrete sugars from their roots into the soil, presumably to support beneficial plant‐microbe interactions. Accordingly, manipulation of sugar secretion might be a viable strategy to enhance plant health and productivity. To evaluate the effect of increased root sugar secretion on plant performance and the soil microbiome, we overexpressed glucose and sucrose‐specific membrane transporters in root epidermal cells of the model plant Arabidopsis thaliana . These plants showed strongly increased rates of sugar secretion in a hydroponic culture system. When grown on soil, the transporter‐overexpressor plants displayed a higher photosynthesis rate, but reduced shoot growth compared to the wild‐type control. Amplicon sequencing and qPCR analysis of rhizosphere soil samples indicated a limited effect on the total abundance of bacteria and fungi, but a strong effect on community structure in soil samples associated with the overexpressors. Notable changes included the increased abundance of bacteria belonging to the genus Rhodanobacter and the fungi belonging to the genus Cutaneotrichosporon, while Candida species abundance was reduced. The potential influences of the altered soil microbiome on plant health and productivity are discussed. The results indicate that the engineering of sugar secretion can be a viable pathway to enhancing the carbon sequestration rate and optimizing the soil microbiome. Graphical Abstract and Lay Summary: Plants secrete sugars from their roots to influence the soil microbiome. In this study, the authors demonstrate that plants engineered for increased sugar secretion can increase the abundance and diversity of soil microorganisms. This work could contribute to the breeding of stress‐resistant crop plants.